Implementation Responsibility Character Education at SMP 5 Muhammadiyah Tulangan Studens In Onlne-Based Elearning - Erni Sulisstyowati; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
An online learning system that is currently being implemented at SMP Muhammadiyah 5 Tulangan during the pandemic. In online learning, students are expected to continue to follow the learning schedule and collect assignments according to the time set. So that this online learning will foster the responsibility of students in participating in online learning. In the research process using descriptive qualitative research methods, by understanding social or human problems by analyzing words. The results of this study conclude that even though it is not possible to conduct face-to-face learning due to the covid 19 pandemic, SMP Muhammadiyah 5 Tulangan still carries out online learning well